An online tool for survival prediction of extrapulmonary small cell carcinoma with random forest - Zhang, Xin (Frontiers in Oncology, 2023)
As the corresponding author, thank you very much for giving us an opportunity to revise our manuscript, and I appreciate reviewers very much for their positive and constructive comments and suggestions on the manuscript entitled "An Online Tool for Survival Prediction of Extrapulmonary Small Cell Carcinoma with Random Forest". The manuscript has been revised according to these comments and suggestions. In general, it has been tried best to revise our manuscript and provide the point-by-point responses. All changes were marked in red using the "Track Changes" function in the revised manuscript.The following is a summary list of changes this time (responding to the reviewer 4 and 5):1. Table S3 has been modified into a new form due to the comment 1 of the reviewer 4 to display the stratified random split of training and internal validation cohort is reasonable and two cohort is not significantly different. 2. The included population is adjusted to those diagnosed during 2004-2015 because of the same TNM edition and possible treatment change extrapolated from SCLC. 3. The sample size of the external validation cohort is increased to 68. And since included population is later than 2004, some cases of the external validation cohort before 2004 is also excluded. 4. Some description of performance status was added in the Discussion section.Once again, thank you very much for your comments and suggestions. And we hope that the revised manuscript can be accepted by Frontiers in Oncology. If further revision is necessary, please contact me.